ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO), DAN DANA PIHAK KETIGA (DPK) TERHADAP LOAN TO DEPOSIT RATIO (LDR) (STUDI KASUS PADA BANK BUMN PERSERO DI INDONESIA PERIODE - admin, femj (Jurnal Manajemen Update, 2017)
The study was conducted to examine the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), and Third Party Fund (DPK) on Loan to Deposit Ratio (LDR). The study object is the state-owned Bank Limited Financial Report using the period March 2010 - December 2014. The data analysis technique used in this research is multiple linear regression. Hypothesis testing using f-statistics and t-statistics. The other hand, classical assumption also performed including normality test, linearity test, multicolinearity test, autocorrelation test and heteroscedasticity test. The result in this study indicate that CAR showed no significant effect on LDR. NPL and DPK have significant negative influence on LDR. While BOPO has significant positive influence on LDR. The predictive ability of  four variables to LDR in this study by 58,2%, while as many as 41,8% are influenced by other factors not included in the research model. Keywords: Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Non Performing         Loan (NPL), Operating Expenses to Operating Income (BOPO), and Third      Party Fund (DPK)